Development of Students' Independent Thinking Skills (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Education is a process aimed at educating a person in the spirit of universal and national values, as well as comprehensively developing a person and bringing them to perfection.Thinking is considered a specific product of this process. History and even accumulated experience give us many examples that every person thinks in their own way. Thinking is a product of human consciousness that is expressed in relation to the environment, phenomena in reality, objects and people. Every person has their own way of thinking, their usual way of thinking to evaluate something. And this situation is not only characteristic of a number of people, but is also characteristic of entire peoples, states, and all stages. In every circle of people, in every era, there have been people who think differently from others and look at existence with different eyes. Non-standard thinking forms the basis of almost all discoveries, scientific innovations, and creations. They have always been the reason for the birth of ideas that lead humanity to progress.